2014
DOI: 10.1002/app.41740
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the nanofiber dimensions on the properties of nanocellulose/poly(vinyl alcohol) aerogels

Abstract: The investigation of aerogels made from cellulose nanofibers and poly(vinyl alcohol) (PVOH) as a polymeric binder is reported. Aerogels based on different nanocellulose types were studied to investigate the influence of the nanocellulose dimensions and their rigidity on the morphology and mechanical properties of the resulting aerogels. Thus, cellulose nanocrystals (CNCs) with low (10), medium (25), and high (80) aspect ratios, isolated from cotton, banana plants, and tunicates, respectively, microfibrillated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 63 publications
(116 reference statements)
1
21
0
Order By: Relevance
“…For the past few years, the preparation of cellulose nanocrystals (CNCs) and their application in composite materials have gained increasing attention because of their inherent properties like outstanding mechanical properties (elastic modulus of 130-150 GPa) (Iwamoto et al 2009), high specific surface area (up to several hundreds of m 2 /g) (Ng et al 2015), high length-to-width ratio (up to several hundreds) (Jonoobi et al 2015) combined with low density (1.6 g/cm 3 ) (Moon et al 2011), low thermal expansion (0.1 ppm K -1 ) (Song et al 2013), biodegradability and renewability. Due to their special intrinsic nanostructure and excellent properties, CNCs have wide application potential in nanomaterials, such as aerogels (Mueller et al 2015;yang et al 2015), biomedical materials (Domingues et al 2014;Dugan et al 2013;Jorfi and Foster 2015;Plackett et al 2014), packaging materials (Fortunati et al 2012;Li et al 2013b;Mihindukulasuriya and Lim 2014), optical (Biyani et al 2013;Schlesinger et al 2015) or electroconductive (Lyubimova et al 2015;Ning et al 2015;Shi et al 2013;Tang et al 2014) materials, and several mechanically reinforced nanocomposites (de Castro et al 2015;Habibi 2014;Jonoobi et al 2015;Ng et al 2015;Sapkota et al 2015;Therien-Aubin et al 2015;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, the preparation of cellulose nanocrystals (CNCs) and their application in composite materials have gained increasing attention because of their inherent properties like outstanding mechanical properties (elastic modulus of 130-150 GPa) (Iwamoto et al 2009), high specific surface area (up to several hundreds of m 2 /g) (Ng et al 2015), high length-to-width ratio (up to several hundreds) (Jonoobi et al 2015) combined with low density (1.6 g/cm 3 ) (Moon et al 2011), low thermal expansion (0.1 ppm K -1 ) (Song et al 2013), biodegradability and renewability. Due to their special intrinsic nanostructure and excellent properties, CNCs have wide application potential in nanomaterials, such as aerogels (Mueller et al 2015;yang et al 2015), biomedical materials (Domingues et al 2014;Dugan et al 2013;Jorfi and Foster 2015;Plackett et al 2014), packaging materials (Fortunati et al 2012;Li et al 2013b;Mihindukulasuriya and Lim 2014), optical (Biyani et al 2013;Schlesinger et al 2015) or electroconductive (Lyubimova et al 2015;Ning et al 2015;Shi et al 2013;Tang et al 2014) materials, and several mechanically reinforced nanocomposites (de Castro et al 2015;Habibi 2014;Jonoobi et al 2015;Ng et al 2015;Sapkota et al 2015;Therien-Aubin et al 2015;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…CNCs can further form lyotropic phases, display a high surface area, and the abundance of surface hydroxyl groups makes the chemical modification of the surface readily possible. All these features make CNCs and other nanocellulose types interesting for a broad range of new applications including, use as a reinforcing filler in polymer nanocomposites [35, 36], the basis for stimuli responsive materials [9, 37, 38], as a nucleating agent [39, 40], a carrier for the controlled delivery of molecules [41], biosensors [42], and a component of tissue engineering scaffolds [43, 44]. In addition, the substitution of microcrystalline cellulose, which has long been used as rheology modifier in food products and cosmetic formulations, and as an excipient in tablets, with nanocellulose types can be envisioned to bring significant benefits beyond those described above.…”
Section: Introductionmentioning
confidence: 99%
“…The improved modulus of clay/NCC hybrid aerogels may be caused by the interaction between the negatively charged sulfonate groups on the NCC and the positively charged sodium atoms as the counterions on the surface of the clay platelets, along with hydrogen bonding between NCC and clay . Furthermore, poly(vinyl alcohol) has also been demonstrated as a polymer binder to consolidate the network . Yang et al proposed a hydrazone cross‐linked NCC aerogel from orthogonally functionalized NCC with hydrazide and aldehyde groups (Figure c) .…”
Section: Fabrication Of Pnas and Their Propertiesmentioning
confidence: 99%
“…Generally, Young's moduli of PNAs increase with the density. Mueller et al found that the higher aspect ratio and moduli of nanofibers resulted in higher Young's moduli of PNAs from nanocelluloses when the content of cross‐linker was less than that of nanofibers. If an increasing concentration of cross‐linker was employed, this effect would be suppressed.…”
Section: Fabrication Of Pnas and Their Propertiesmentioning
confidence: 99%